Illiberal Jewish-Christian Encounters: Political Temporalities in Amish Country Tourism - Feldman, Rachel Z. (Journal of the American Academy of Religion, 2024)
Increasing numbers of ultra-Orthodox Jews are flocking to Lancaster County, Pennsylvania, to participate in Amish country tourism and to consume kosher dairy products, sometimes produced through economic collaborations between Orthodox Jews and local Amish/Mennonite farmers. Through an ethnographic examination of these phenomena, we demonstrate how Amish tourism fosters illiberal interreligious encounters among the triangle of ultra-Orthodox Jewish tourists, Amish/Mennonite farmers, and Christian tour guide mediators. Whereas historically tourism to the Amish was driven by white nostalgic longings for a European peasant past and the American frontier, Orthodox Jews project a nostalgic vision of the Eastern European shtetl onto the Amish and their dairy products. We borrow the concept of political temporalities (Little 2022) to explore an illiberal political temporality formed by the encounter among illiberal religious groups in a recreational tourist setting. Despite different nostalgic projections, these religious groups converged over their visions of an American religious present and future.